2013
DOI: 10.1088/0004-637x/778/2/120
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Measurement of the Spin-Down of Calvera: A Radio- And Gamma-Ray-Quiet Pulsar

Abstract: We measure spin-down of the 59 ms X-ray pulsar Calvera by comparing the XMM-Newton discovery data from 2009 with new Chandra timing observations taken in 2013. Its period derivative isṖ = (3.19 ± 0.08) × 10 −15 , which corresponds to spin-down luminosityĖ = 6.1 × 10 35 erg s −1 , characteristic age τ c ≡ P /2Ṗ = 2.9 × 10 5 yr, and surface dipole magnetic field strength B s = 4.4 × 10 11 G. These values rule out a mildly recycled pulsar, but Calvera could be an orphaned central compact object (anti-magnetar), w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(67 citation statements)
references
References 34 publications
2
65
0
Order By: Relevance
“…Interestingly, the calculations given in Shibanov et al (1995) result in a similar dependence of the pulsed fraction on photon energy as observed for Calvera. Namely, Halpern et al (2013) found that the pulsed fraction is ≈ 10% at energies below 0.5 keV and ≈ 30% above 0.5 keV, which is in accord with the pulsed fraction calculated for the NS with dipole magnetic field B = 10 12 G covered by the hydrogen atmosphere .…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, the calculations given in Shibanov et al (1995) result in a similar dependence of the pulsed fraction on photon energy as observed for Calvera. Namely, Halpern et al (2013) found that the pulsed fraction is ≈ 10% at energies below 0.5 keV and ≈ 30% above 0.5 keV, which is in accord with the pulsed fraction calculated for the NS with dipole magnetic field B = 10 12 G covered by the hydrogen atmosphere .…”
Section: Discussionsupporting
confidence: 86%
“…Assuming a magnetic field B = 10 12 G, they obtain good fits in spite of the viewing geometry. These results are broadly consistent in the sense that T ∞ ∼ 200 eV for blackbody models and T ∞ 100 eV for NSA models and emission area R ∞ /d = 2 − 4 km kpc −1 (Rutledge et al 2008;Shevchuk et al 2009;Zane et al 2011;Halpern et al 2013;Shibanov et al 2016). In our SSA model, we obtain a higher temperature at 0.6 keV and rather unconstrained radius R ∞ /d = 0.4 − 10 km kpc −1 .…”
Section: Xmm-newtonsupporting
confidence: 84%
“…As is shown in Shevchuk et al (2009), Zane et al (2011) and Halpern et al (2013), single thermal spectra, either blackbody or pure hydrogen atmospheric model (NSA), can not provide decent fit, and two thermal components is required. The first joint fit for all available data is performed by Shibanov et al (2016), who use a single component magnetized hydrogen atmosphere model to account for the inhomogeneities of the stellar surface.…”
Section: Xmm-newtonmentioning
confidence: 99%
See 1 more Smart Citation
“…Calvera is also unique in that it is the only energetic pulsar that emits virtually no radio nor gamma radiation, which places constraints on models for particle acceleration in magnetospheres [170].…”
Section: Radio Quiet Neutron Starsmentioning
confidence: 99%